1998
DOI: 10.1038/bjc.1998.316
|View full text |Cite
|
Sign up to set email alerts
|

Do mast cells help to induce angiogenesis in B-cell non-Hodgkin's lymphomas?

Abstract: Summary Morphological and morphometric data showing a higher number of mast cells (MCs) in the stroma of B-cell non-Hodgkin's lymphomas (B-NHL) than in benign lymphadenopathies are presented in support of the suggestion that angiogenesis during the progression of B-NHL may be partly mediated by angiogenic factors in their secretory granules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Moreover, tryptase activates latent metalloproteinases and plasminogen activator, 22 which degrade the extracellular matrix, where angiogenic cytokines, such as FGF-2, are stored. 23 MC are strikingly associated with angiogenesis in tumors, namely hemangioma, carcinomas, lymphoma and multiple myeloma, [10][11][12] where they are preferentially accumulated in peripheral areas and within the surrounding connective tissue, and rest near or around blood or lymphatic vessels. MC are recruited and activated via several factors secreted by tumor cells: the c-kit receptor, FGF-2, VEGF and platelet-derived endothelial cell growth factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, tryptase activates latent metalloproteinases and plasminogen activator, 22 which degrade the extracellular matrix, where angiogenic cytokines, such as FGF-2, are stored. 23 MC are strikingly associated with angiogenesis in tumors, namely hemangioma, carcinomas, lymphoma and multiple myeloma, [10][11][12] where they are preferentially accumulated in peripheral areas and within the surrounding connective tissue, and rest near or around blood or lymphatic vessels. MC are recruited and activated via several factors secreted by tumor cells: the c-kit receptor, FGF-2, VEGF and platelet-derived endothelial cell growth factor.…”
Section: Discussionmentioning
confidence: 99%
“…8 MC density is highly correlated with the extent of both normal and pathological angiogenesis, such as that in chronic inflammatory diseases and tumors. 9 We have demonstrated that in multiple myeloma and B cell non-Hodgkin's lymphoma there is a striking association between MC and microvessel counts and that both increase in function of tumor progression, as defined by its increasing malignancies grades, 10,11 while in both benign lymphadenopathies and in B cell non-Hodgkin's lymphoma angiogenesis is highly correlated with the total and MC tryptase-positive counts. 12 Tryptase contained in MC secretory granules is angiogenic both in vitro and in vivo experimental models, and specific tryptase inhibitors suppress this activity.…”
Section: Introductionmentioning
confidence: 94%
“…MCs are strikingly associated with angiogenesis, as found in chronic inflammatory diseases, namely rheumatoid arthritis and psoriasis, and in tumours, namely haemangiomas, carcinomas and lymphomas (Meininger and Zetter, 1992;Norrby and Woolley, 1993;Qu et al, 1995;Ribatti et al, 1998). In tumours, MCs are recruited and activated via several factors secreted by tumour cells: the c-kit receptor, or stem cells factor (Poole and Zetter, 1983;Norrby and Wooley, 1993), as well as the basic fibroblast growth factor (FGF-2), vascular endothelial growth factor (VEGF-A) and platelet-derived endothelial cell growth factor (Gruber et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Increased lymph node and bone marrow angiogenesis was found in patients with lymphoma, with progression from benign lymphadenopathies to low-grade and intermediate-grade lymphomas, and accompanied by simultaneous increases in macrophage and mast cell bone marrow density. [5][6][7] Increased marrow vascularity was reported in patients with acute lymphoblastic and myelogenous leukemias, myelodysplastic syndrome, and myeloproliferative diseases. [8][9][10][11] Our own study found increased vascularity in bone marrow from patients with myelodysplastic syndrome (MDS) and all types of leukemia, except chronic lymphocytic leukemia.…”
Section: Introductionmentioning
confidence: 99%